1972
DOI: 10.1177/00220345720510041101
|View full text |Cite
|
Sign up to set email alerts
|

14C-Eugenol: I. Synthesis, Polymerization, and Use

Abstract: The mixture of eugenol and zinc oxide resulted in a lignin-like polymer; this was verified by spectroscopy. 14C-eugenol with high specific activity was synthesized and administered intraperitoneally to rats. 14C-eugenol was subsequently found in all tissues. Chromatography was used for separation and quantitation of this compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Historically eugenol has been used to treat dental problems due to its analgesic, anesthetic, anti-inflammatory and antibacterial effects 41 42 . Previous studies have shown that eugenol is absorbed into the tissues of rats, including the intestine 43 44 . Given this, we appreciate the possibility that the effects we describe of diet supplementation with eugenol may be a direct interaction with intestinal tissue stimulating mucus secretion, independent of the microbial changes we characterize.…”
Section: Discussionmentioning
confidence: 99%
“…Historically eugenol has been used to treat dental problems due to its analgesic, anesthetic, anti-inflammatory and antibacterial effects 41 42 . Previous studies have shown that eugenol is absorbed into the tissues of rats, including the intestine 43 44 . Given this, we appreciate the possibility that the effects we describe of diet supplementation with eugenol may be a direct interaction with intestinal tissue stimulating mucus secretion, independent of the microbial changes we characterize.…”
Section: Discussionmentioning
confidence: 99%
“…29 Even after the end of the setting reaction, eugenol release leads to selfoxidation and becomes darker with time. 30 Moreover, ZOE sealers present increased solubility. 31,32 This type of crown discoloration has been characterized as chemical discoloration.…”
Section: Discussionmentioning
confidence: 99%
“…Free or even bound eugenol changes chemically (oxidizes) and darkens with time. [1023] Although AH Plus is silver-free and advertised as nonstaining compared to its predecessor AH26, it caused more overall coronal discoloration (grayish discoloration) than Apexit Plus sealer (reddish brown discoloration). Some authors found the same results but with AH26 sealer.…”
Section: Discussionmentioning
confidence: 99%